Will Artificial Intelligence Replace Project Managers? A Case Study on the Use of Three Leading Tools: Wrike AI, JIRA With Atlassian Intelligence, and Microsoft Project With Copilot AI - Ząb, Ewelina (Czy sztuczna inteligencja zastąpi menedżerów projektów? Studium przypadku zastosowania trzech wiodących narzędzi: Wrike AI, JIRA z Atlassian Intelligence i Microsoft Project z Copilot AI, 2024)
Aim: This study explores the impact of artificial intelligence (AI) on the role of project managers, focusing on the analysis of three key AI-powered tools: Wrike AI, JIRA with Atlassian Intelligence, and Microsoft Project with Copilot AI. It also examines how these tools are shaping the evolution of project managers’ skills. Methodology: The research methodology includes a literature review and critical analysis of the selected tools, examining their capabilities in automating tasks, enhancing risk analysis, and generating reports. Results: The study shows that AI significantly enhances efficiency and decision-making in project management, especially in automating routine tasks. However, complete automation cannot replace human skills in managing complex projects. Implications and recommendations: Project managers must develop competencies in AI collaboration, data analysis, and ethical considerations. Future research should explore the evolving role of AI in supporting more complex project management tasks. Originality/value: This study offers valuable insights into integrating AI in project management, highlighting the need for a balanced approach between automation and human expertise.
Business Informatics = Informatyka Ekonomiczna, 2024, Nr 1-2 (67-68), s. 106-116
Keywords: artificial intelligence; project management; automation; decision-making; collaboration; sztuczna inteligencja; zarządzanie projektami; automatyzacja; podejmowanie decyzji; współpraca